2007
DOI: 10.1021/jp0740954
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Investigation of the Complexes between Bromobenzene and Several Electron Donors:  Some Insights into the Magnitude and Nature of Halogen Bonding Interactions

Abstract: Halogen bonding, a specific intermolecular noncovalent interaction, plays crucial roles in fields as diverse as molecular recognition, crystal engineering, and biological systems. This paper presents an ab initio investigation of a series of dimeric complexes formed between bromobenzene and several electron donors. Such small model systems are selected to mimic halogen bonding interactions found within crystal structures as well as within biological molecules. In all cases, the intermolecular distances are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
127
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(140 citation statements)
references
References 58 publications
13
127
0
Order By: Relevance
“…[23,25,27,29,[33][34][35][36][37][38][39] Halogen bonding has recently been recognised as a significant interaction in molecular recognition and self-assembly processes, [40,41] and is therefore employed for a wide range of applications in materials, [42][43][44][45] synthetic [46][47][48] and medicinal chemistry. [49][50][51][52] Concerning the fundamentals of halogen bonding, recent studies have focused mainly on structural determinations [18][19][20][21][22] and on quantum mechanical calculations of the bond energy in vacuo at 0 K. [25][26][27][28][29][30][31][53][54][55][56][57][58][59][60] The experimental knowledge of the thermodynamics of the halogen bond at room temperature in solution shows a marked contrast between inorganic and organic halogen-bond donors. In addition to the thousand complexation constants for diiodine, [1] about ...…”
Section: Introductionmentioning
confidence: 99%
“…[23,25,27,29,[33][34][35][36][37][38][39] Halogen bonding has recently been recognised as a significant interaction in molecular recognition and self-assembly processes, [40,41] and is therefore employed for a wide range of applications in materials, [42][43][44][45] synthetic [46][47][48] and medicinal chemistry. [49][50][51][52] Concerning the fundamentals of halogen bonding, recent studies have focused mainly on structural determinations [18][19][20][21][22] and on quantum mechanical calculations of the bond energy in vacuo at 0 K. [25][26][27][28][29][30][31][53][54][55][56][57][58][59][60] The experimental knowledge of the thermodynamics of the halogen bond at room temperature in solution shows a marked contrast between inorganic and organic halogen-bond donors. In addition to the thousand complexation constants for diiodine, [1] about ...…”
Section: Introductionmentioning
confidence: 99%
“…These interactions, often referred to as halogen bonding, [1,2] not only involve dihalogens of the types X 2 and XY, [3][4][5][6][7] but also appear for a variety of carbon-bound halogen atoms occurring in alkyl and aryl halides. [3][4][5][6] These non-covalent interactions between the carbon-bound halogen atoms and electron donors have been proven to be an essential driving force for crystal engineering and supramolecular self-assembly, [7][8][9][10][11][12][13][14] molecular recognition, [15][16][17][18] and various biochemical processes, [19][20][21][22] and, consequently, have been the subject of a variety of experimental and theoretical studies. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Experimental studies involving CÀhalogen···Y interactions tend to concentrate on Lewis bases Y in which the electron donor atom is nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…MP2 calculations of the halogen bond of bromobenzene have recently been reported. [71] Ab initio calculations of the complexes of aromatic molecules have shown that a very large basis set near saturation and CCSD(T) level electron correlation is necessary for a quantitative evaluation of the intermolecular interaction energies of aromatic molecules. [87][88][89][90] Unfortunately, however, calculations on the halogen bond of aryl halide molecules at the CCSD(T) level have not been reported.…”
mentioning
confidence: 99%
“…[68,72,73] On the other hand, it has been stressed repeatedly that charge-transfer (orbital-orbital) interactions are an important source of the attraction in halogen bonds. [7,[69][70][71][72][73][74][75][76][77][78][79] The strong correlation between the electron-density transfer and the interaction energy suggests that charge-transfer interactions play important roles in the attraction. The chargetransfer contribution can explain the directionality of the halogen bond.…”
mentioning
confidence: 99%